Contrasts in intermittent endurance performance and heart rate response between female and male soccer players of different playing levels - Araújo, Maithe; Baumgart, Christian; Freiwald, Jürgen; Hoppe, Matthias (Biology of Sport, 2019)
This study compared intermittent endurance performance and heart rate (HR) response, as well as their relationship, by sex and competitive level in soccer. A total of 68 outfield (18 elite and 16 sub-elite female, 17 elite and 17 sub-elite male) soccer players performed the Interval Shuttle Run Test (ISRT) with monitored HR. Sex and level effects were evaluated by two-way analysis of variance (ANOVA) and the relationships between parameters using Pearson’s correlation coefficient. Female players presented lower performance (effect sizes [ES]: 2.12-4.71, p < 0.01) and higher submaximal HR during the ISRT (ES: 1.66-3.40, p < 0.01). Elite players showed higher performance and reduced submaximal HR compared with their sub-elite counterparts, with a large level effect only evident between the female groups (ES: 1.22-1.56, p < 0.01). The maximum and the HR recovery 1 min after the ISRT (HRR) did not differ among all groups (ES: 0.01-0.51, p ≥ 0.18). The HRR was slightly related to the test performance for all groups (r = 0.20, p = 0.12). Large to very large negative correlations were verified between HR at 6 and 9 min during the ISRT and the test performance for each group (r = -0.54 to -0.84, p ≤ 0.04). However, 16 (3 elite and 13 sub-elite) female players did not reach the 9th minute of the test. The gap between competitive levels among female soccer players is greater than that observed for male players in intermittent endurance performance and submaximal HR response. The HRR had only a minor impact on performance and was influenced neither by sex nor by level.